2005
DOI: 10.1080/13880200590951856
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antidiarrheal Potential ofEmblica officinalis.

Abstract: The antidiarrheal potential of the methanol extract of the fruit of Emblica officinalis. Gaertn. Euphorbiaceae was evaluated using several experimental models of diarrhea in Wistar albino rats. The methanol extract showed a significant inhibitory effect on rats with diarrhea induced by castor oil and magnesium sulfate. The methanol extract produced a significant reduction in gastrointestinal motility in charcoal meal tests in rats. It also significantly inhibited PGE-induced enteropooling as compared to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The observed antidiarrheal activity of Phyllanthus emblica fruit extract in two species, such as, in rats, mediated through inhibition of prostaglandins action (Perianayagam et al, 2005) and in mice through antimuscarinic and Ca 2+ antagonist effects, provides a sound mechanistic base for its effectiveness in diarrhea. This is also in accordance with the general understanding that plants contain multiple active constituents with effect enhancing activities (Gilani and Rahman, 2005).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The observed antidiarrheal activity of Phyllanthus emblica fruit extract in two species, such as, in rats, mediated through inhibition of prostaglandins action (Perianayagam et al, 2005) and in mice through antimuscarinic and Ca 2+ antagonist effects, provides a sound mechanistic base for its effectiveness in diarrhea. This is also in accordance with the general understanding that plants contain multiple active constituents with effect enhancing activities (Gilani and Rahman, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Antimuscarinic drugs and CCBs are known to be effective as antispasmodic, anti-motility and antidiarrheal (Lee et al, 1997;Brown and Taylor, 2006;Pasricha, 2006). Hence, the presence of dually acting spasmolytic activity in the plant extract might be contributing towards its effectiveness in diarrhea and abdominal spasm, in addition to the reported antidiarrheal activity related with inhibition of prostaglandins synthesis (Perianayagam et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Perianayagam have demonstrated that methanolic extract of fruits of Emblica officinalis reduces gastrointestinal motility and PGE2mediated accumulation of intestinal fluid (enteropooling) which can be related to the presence of tannins in Emblica officinalis extract [35]. Long term administration of Emblica officinalis facilitated myocardial adjustment by boosting endogenous antioxidants and safe guard the rat hearts from oxidative stress coupled with ischemicreperfusion injury [36].…”
Section: Emblica Officinalismentioning
confidence: 99%
“…Khan, have described that Emblica officinalis is enlisted as a fundamental plant in Indian indigenous scheme of medication. It belongs to family Euphorbiaceae[26]. It is generally named as Amla, Indian gooseberry or Phyllanthus Emblica.…”
mentioning
confidence: 99%